Isolasi dan Karakterisasi Actinomycetes Sebagai Penghasil Antibiotik Dari Sampel Tanah Pada Peternakan Sapi di Kecamatan Galesong Kabupaten Takalar - Hasyim, Adriani; Febriwanti Tulak, Yessica (Jurusan Biologi UIN Alauddin Makassar, 2013)
A research on the isolation and characteristics of the antibiotic-producing actinomycetes from soil sample on dairy farms in the district Galesong Takalar has been done for obtaining antibioticproducing actinomycetes isolates. This study is an exploratory study with laboratory. This research method is the agar diffusion method. Isolation was conducted using scratch method, 7x24 hour incubation period. Isolates obtained was purified on a medium Glycerol Yeast Extract Agar (GYEA).Isolates fermented for 7x24 hours on the tube with the intensity of 170 rpm at room temperature. Fermentation result was tested for antibiotic activity. Both isolates were effective as an antibiotic against bacteria used in the test.Keywords: Actinomycetes, antibiotics, characterization, isolation, soil, Takalar